Fabrication of 3-stepped spiral trench with smooth sidewall at nano-level to deposit superconducting material for energy storage. (23rd May 2019) - Sasaki, Minoru; Hsu, Che-Wei; Suzuki, Yasuhiro; Hioki, Tatsumi; Noh, Joo-hyong; Takai, Osamu; Watanabe, Hideo; Doy, Hideyuki; Motohiro, Tomoyoshi
Fabrication techniques consisting of patterning imbedded masks, Si etching, and smoothing treatment for realising 3-stepped spiral trench with smooth sidewall is described. This trench is subsequently filled with the superconducting material of the sputter-deposited NbN and the electroplated Cu. After polishing, the trench space becomes the coil for the superconducting magnetic energy storage. The important points of the trench quality are the certain connection between two coil ends, and the smooth sidewall at nano-level. Both demanded performances are met with the fail-safe designing and processing.